Short-Term Distribution System Planning Using a System Reduction Technique - Melgar-Dominguez, Ozy D.; Salas, Richard W.; Mantovani, Jose R. Sanches (IEEE access, 2021)
Given the necessity of developing more efficient electric distribution systems (EDSs) and providing a continuous energy service for active and passive users, distribution system planners are constantly seeking for more robust planning strategies that can address the complexities of large-scale EDSs. In this regard, the proposed work investigates the implementation of a novel strategy that is based on two stages to tackle the short-term planning problem in large-scale EDSs. In the first stage, a system reduction technique is developed to remove all non-desired buses and circuits from the original large-scale EDS, while in the second stage an optimization model is formulated to represent the EDS expansion planning problem. The planning stage is designed using a multi-period formulation, which defines, in the most cost-effective way, actions such as the allocation of voltage regulators (VRs) and capacitor banks (CBs) to improve the EDS operation, considering the demand growth and new requests for distributed generation (DG) connections. The objective function of this optimization model minimizes the expected cost of energy purchased from the market and charges due to carbon emission taxes, while the energy purchased from DG developers is maximized. For simulation purposes, a real 1080-bus EDS is reduced to an equivalent 54-bus system and implementing the developed optimization model, results show that a set of planning actions can be obtained to improve the EDS operation. These obtained planning actions are projected to the 1080-bus EDS and using an optimal power flow tool, the accuracy of the proposed planning strategy is estimated.